2017
DOI: 10.1038/ncomms15844
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of the shape of graphene nanobubbles on trapped substance

Abstract: Van der Waals (vdW) interaction between two-dimensional crystals (2D) can trap substances in high pressurized (of order 1 GPa) on nanobubbles. Increasing the adhesion between the 2D crystals further enhances the pressure and can lead to a phase transition of the trapped material. We found that the shape of the nanobubble can depend critically on the properties of the trapped substance. In the absence of any residual strain in the top 2D crystal, flat nanobubbles can be formed by trapped long hydrocarbons (that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
70
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(75 citation statements)
references
References 42 publications
4
70
1
Order By: Relevance
“…Many applications of 2D materials involve multiple transfer processes of 2D materials to a substrate, by which 2D material blisters, such as bubbles and tents, frequently form by trapping water, gas, or solid nanoparticles at the interface ( Figure ) . Initially, these circular blisters have been viewed as an inconvenience for device applications .…”
Section: Out‐of‐plane Modementioning
confidence: 99%
See 3 more Smart Citations
“…Many applications of 2D materials involve multiple transfer processes of 2D materials to a substrate, by which 2D material blisters, such as bubbles and tents, frequently form by trapping water, gas, or solid nanoparticles at the interface ( Figure ) . Initially, these circular blisters have been viewed as an inconvenience for device applications .…”
Section: Out‐of‐plane Modementioning
confidence: 99%
“…However, recent studies have shown considerable in‐plane strain associated with these out‐of‐plane bubbles and tents, which creates opportunities for the study of new fundamental physics and applications of 2D materials emerging at large strain level . Alternatively, many 2D material bubbles and tents are designedly created by confining interface liquid and prepatterning substrates (Figure b), respectively. Famous examples include the highly strained bubble‐like and tent‐like graphene, which have been shown to possess large pseudo‐magnetic fields, up to 300 T (Figure c), as well as 2D semiconductors draping over an array of micropillars, which can be applied as large‐scale quantum emitters (Figure d) …”
Section: Out‐of‐plane Modementioning
confidence: 99%
See 2 more Smart Citations
“…Encapsulated SLG and other layered material heterostructures are assembled by first producing the individual layered materials on separate substrates, typically Si + SiO 2 19 , or polymers, such as Polymethyl methacrylate (PMMA) 18,30 , followed by transfer and stacking to achieve the desired heterostructure 18,19,30 . During stacking, contaminants such as hydrocarbons 31 , air 23 , or water 32,33 , can become trapped between the layers, aggregating into spatially localized pockets with typical lateral sizes from a few nanometers 34 up to micrometers 23 , known as blisters 23 or bubbles 19,20,31 , which form due to the interplay of the layered material elastic properties and van der Waals forces 34 . This aggregation of contaminants into blisters leaves the regions located between them with clean interfaces 31 , and devices can therefore be fabricated exploiting these areas 30 .…”
Section: Introductionmentioning
confidence: 99%